Participation in Advance Care Planning and Associated Factors among Surrogate Decision Makers of Patients with Hematologic Malignancies - WANG Tianhang, WANG Wen, SHEN Wenting, SHI Baoxin (Zhongguo quanke yixue, 2022)
BackgroundAdvance care planning (ACP) helps patients to obtain medical care meeting their values, goals and preferencesunder the circumstances of loss of decision-making ability. The surrogate decision maker (SDM) plays a key role as the main participantinvolved in the process of ACP. But there are no studies on the participation and role of SDMs in ACP process in China.ObjectiveTo investigate the participation in ACP of SDMs of patients with hematologic malignancies and its associated factors, providing a reference for the development of localized strategies for ACP implementation, and for the promotion of ACP in China.MethodsConvenient sampling was used to select the SDMs of 235 patients with hematologic malignancies recruited from Blood Diseases Hospital, Chinese Academy of Medical Sciences during October 2020 to March 2021. They were invited to compete a survey using the Chinese version of the 17-item Advance Care Planning Engagement Survey for Surrogate Decision Makers (C-ACP-SDM-17) , Chinese version of Mishel Uncertainty in Illness Scale-Family Member form (C-MUIS-FM) , Simplified Coping Style Questionnaire (SCSQ) , and Social Support Rating Scale (SSRS) . The C-ACP-SDM-17 scores were compared by demographic factors of the SDMs. Pearson correlation analysis was used to explore the correlation of C-ACP-SDM-17 score with C-MUIS-FM, SCSQ, and SSRS scores of SDMs. Multiple linear regression was used to analyze the factors associated with the participation in ACP of SDMs.ResultsThe average total scores of the C-ACP-SDM-17, C-MUIS-FM, and SSRS of the SDMs were (52.23±13.57) , (66.43±12.54) and (40.33±6.78) , respectively. And the average scores of two subscales of SCSQ of the SDMs, active coping and passive coping, were (24.34±6.94) , and (9.87±4.25) , respectively. Male, having experience of involvement in end-of-life medical decision making, awareness of life-sustaining treatment, and knowing of ACP were associated with statistically higher C-ACP-SDM-17 score of SDMs (P<0.05) . The total C-ACP-SDM-17 score of SDMs was negatively correlated with the total score of C-MUIS-FM, and scores of its two subscales, uncertainty and ambiguity, but was positively correlated with the score of active coping. Gender, involvement in end-of-life medical decision making, awareness of life-sustaining treatment, hearing about ACP, level of disease uncertainty, and level of active coping were factors associated with the involvement of SDMs in ACP (P<0.05) .ConclusionThe ACP participation in SDMs of hematologic malignancies patients was above average. To increase their participation level, it is suggested for medical workers to encourage hematologic malignancies patients' male family members or family members with experience of involvement in end-of-life medical decision making to be SDMs, and give them ACP education, explanation of hematologic malignancies, as well as guide them to actively cope with the pressure of decision making.